2018
DOI: 10.3389/fmars.2018.00210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Fe-Ligands, Released by Emiliania huxleyi, on Fe(II) Oxidation Rate in Seawater Under Simulated Ocean Acidification Conditions: A Modeling Approach

Abstract: The potential effect of ocean acidification on the exudation of organic matter by phytoplankton and, consequently, on the iron redox chemistry is largely unknown. In this study, the coccolithophorid Emiliania huxleyi was exposed to different pCO 2 conditions (225-900 µatm), in order to determine the role of natural organic ligands on the Fe(II) oxidation rate. Oxidation kinetics of Fe(II) were studied as a function of pH (7.75-8.25) and dissolved organic carbon levels produced (0-141.11 µmol C L −1 ) during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 105 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…Microcystis aeruginosa (Lee et al, 2017), coccolithophore Emiliania huxleyi (Samperio-Ramos et al, 2018a), and diatoms Chaetoceros radicans (Lee et al, 2017) and Phaeodactylum tricornutum (Santana-Casiano et al, 2014) have all been found to retard Fe(II) oxidation rates. Furthermore, the effect of cellular exudates on the reaction constant appears to scale with increasing total organic carbon (Samperio-Ramos et al, 2018b).…”
Section: Fe(ii) Decay Experimentsmentioning
confidence: 99%
“…Microcystis aeruginosa (Lee et al, 2017), coccolithophore Emiliania huxleyi (Samperio-Ramos et al, 2018a), and diatoms Chaetoceros radicans (Lee et al, 2017) and Phaeodactylum tricornutum (Santana-Casiano et al, 2014) have all been found to retard Fe(II) oxidation rates. Furthermore, the effect of cellular exudates on the reaction constant appears to scale with increasing total organic carbon (Samperio-Ramos et al, 2018b).…”
Section: Fe(ii) Decay Experimentsmentioning
confidence: 99%